2020
DOI: 10.48550/arxiv.2005.07640
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optical lattice platform for the SYK model

Chenan Wei,
Tigran A. Sedrakyan

Abstract: The tractability of the Sachdev-Ye-Kitaev (SYK) model at large N limit makes it ideal to theoretically study its chaotic non-Fermi liquid behavior and holographic duality properties. We show that complex SYK Hamiltonian emerges from a system of spinless itinerant fermions in optical Kagome lattice with a strong disorder. We discuss the regimes supporting flat band spectra in Kagome lattice, where the system can be non-dispersive. Random interaction between non-dispersive fermions is induced due to randomly dis… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…This is inspired by Ref. [39], but the same symmetry setting might be relevant in other platforms such as cold atoms [40,41] or spin chain [42] realizations.…”
Section: Experimental Platforms and Form Of Interactionsmentioning
confidence: 99%
“…This is inspired by Ref. [39], but the same symmetry setting might be relevant in other platforms such as cold atoms [40,41] or spin chain [42] realizations.…”
Section: Experimental Platforms and Form Of Interactionsmentioning
confidence: 99%
“…[28] have shown the existence of isolated flat bands and spin-1 conical bands with a flat band located at E = 0 employing staggered flux phases ψ + and ψ − on the up and down triangles of the kagome lattice. A recent work [38] considering the same flux ψ on the up and down triangles of the kagome lattice has shown that the flat band in the model can also be tuned from top to middle to bottom when changing the flux ψ. The current results on the conditions for the existence of flat bands and its tunability certainly will enrich the flat band physics in kagome lattice from Abelian to non-Abelian regime.…”
Section: B Location-tuable Flat Bandsmentioning
confidence: 99%
“…These effects have been identified as characteristic signatures of the wormhole phase. Significant efforts have been made to physically realize the SYK model in atomic [18], optical [19], and solid-state [20][21][22] platforms, or using quantum simulators [23,24]. Proposals for implementing and observing the wormhole physics in the MQ model and its complex fermion variants have also been made [8,25,26].…”
Section: Introductionmentioning
confidence: 99%